EFEITO GASTROPROTETOR DE NANOCÁPSULAS COM NARINGINA E NARINGENINA EM ÚLCERA GÁSTRICA INDUZIDA POR INDOMETACINA EM RATOS WISTAR - Pohl, Ariane Ribas (2017)
Non-steroidal anti-inflammatory drugs (NSAIDs) are used in the treatment of pain, fever and inflammatory processes. However, these drugs have some adverse effects on the gastrointestinal tract. Indomethacin (INDO) may cause adverse reactions to the patient, such as gastric erosions and ulcers. Oxidative stress occurs when the cellular antioxidant defense mechanism is no longer able to inactivate reactive oxygen species (ROS) or excess production. Oxidative stress leads to severe damage to DNA, which has been associated with several pathologies, including gastric ulcers. Antioxidants are able to fight these reactive species, thus protecting biomolecules and reducing disease risk. Flavonoids are the plant metabolites that provide protection against ROS. Naringin (NA) and naringenin (NG) are flavonoids responsible for the bitter taste of citrus fruits. They have low solubility in water, they undergo first pass metabolism and low bioavailability when administered orally. Therefore, the importance of nanoencapsulate these flavonoids, to increase stability, changing the pharmacokinetics and biodistribution of these.Nanocapsule suspensions were prepared by the interfacial deposition technique of the preformed polymer. Eight male Wistar rats, divided in control group, omeprazole, NA + NG (L), white nanocapsule (NB), NG + NA (NN) nanocapsule were used. For the induction of ulcer, 48 mg INDO / kg body mass were administered by orogastric gavage. For the pre-treatment groups, omeprazole (5mg / kg body weight) and L (0.5mg of each active, NA and NG), NB (0.5mg of each active, NA and NG) were administered via Oral / day for 28 days. On the 28th day, INDO was administered by v.o. One hour after treatments. All rats were fasted 24 hours prior to induction of gastric injury by INDO. Four hours after INDO administration, rats were euthanized and their stomachs dissected and separated for histological and biochemical analyzes to calculate the gastric and preventive ulcer index, pH determination and oxidative stress parameters, to verify if there was protection By the action of nanocapsules. Pretreatment with NN nanocapsules proved to be more effective than omeprazole in preventing INDO-induced ulcer. More studies are needed so that these assets can be used in therapy.